2012
DOI: 10.1111/j.1600-0722.2012.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate control of pulpal blood flow in the incisor dental pulp of the rat

Abstract: Glutamate is present in primary sensory afferents innervating the dental pulp and is known to exert vasoactive effects. The aims of this study were (i) to assess pulpal blood flow (PBF) after glutamate infusion in the dental pulp and (ii) to observe the distribution of glutamatergic nerve fibers expressing the vesicular transporters of glutamate (VGluT). The PBF was monitored with laser Doppler flowmetry before and after glutamate (0.5 M) infusion in the dental pulp vs. saline infusion. Immunochemistry for VGl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…82 Moreover, previous studies have identified the effective regulation of neurons on dental pulp microcirculation under physiological and pathological conditions. 83,84 Similarly, eNOS-mediated pulp vasodilation is also a valuable response in neurogenic inflammation and involves subsequent release of NO produced in endothelial cells and of inflammatory mediators (e.g., substance P) from sensory nerve endings. 85,86 Angiogenesis, another critical physiological event associated with wound healing and tissue regeneration, involves complex cellular activities correlated with cell proliferation and migration.…”
Section: Anmentioning
confidence: 99%
“…82 Moreover, previous studies have identified the effective regulation of neurons on dental pulp microcirculation under physiological and pathological conditions. 83,84 Similarly, eNOS-mediated pulp vasodilation is also a valuable response in neurogenic inflammation and involves subsequent release of NO produced in endothelial cells and of inflammatory mediators (e.g., substance P) from sensory nerve endings. 85,86 Angiogenesis, another critical physiological event associated with wound healing and tissue regeneration, involves complex cellular activities correlated with cell proliferation and migration.…”
Section: Anmentioning
confidence: 99%
“…In addition to neuropeptides secreted by sensory nerves, glutamate can regulate blood flow in vasodilation. Glutamate transporter-expressing neurons release glutamate into the pulp [69], which binds to the pulp's metabotropic glutamate receptors (GluRs), which regulate pulp blood flow [70].…”
Section: Regulation Of Vascularizationmentioning
confidence: 99%
“…However, VGLUT3 mRNA-positive somas were not detected in the spinal cord [ 31 ]. Interestingly, in rat, pulpal blood flow was regulated by VGLUT3+ nerve terminals [ 33 ], suggesting the possibility of an even more peripheral projection. Moreover, VGLUT3 immunoreactivity was detected in the heart, liver, and kidney but not in intestinal or lung tissue [ 34 ].…”
Section: Characterisation Of Vglut3mentioning
confidence: 99%